The Impact of Board Capabilities on Firm Financial Performance: A Resource-Based View Perspective - Ismail, Aida Maria; Mohd Fauzi, Siti Aisyah Amirah; Yatim, Normahiran (Archives of Business Research, 2022)
The study aims to examine the effect of board capabilities (board composition, board gender diversity and board independence) on firm financial performance in Malaysian public listed companies based on the Resource-Based View Theory (RBVT). The board capabilities are crucial for the investors to create a better organisational performance. The study also used regression analysis to determine the relationships between the variables. The data were extracted from Thomson EikonTM DataStream and annual reports of companies listed under Bursa Malaysia, comprising five years’ worth of information. The results demonstrated a significant impact of board capabilities on firm financial performance. Specifically, board composition and board gender diversity significantly affected firm financial performance. Conversely, board independence and firm financial performance presented no significant impact. Ultimately, the study outlines the essential factors that impact firm financial performance to restore public confidence towards the companies. Hence, the corporate governance factors should be emphasised to protect investors’ interests.